Bee and Tree Temporality in The History of Bees and The Overstory - Anderson, Caitlin (Journal of Ecohumanism, 2022)
The loss of biodiversity through a rapidly changing climate means humans can no longer assume their longevity on Earth; a crisis that has prompted a wave of literary imaginings. This article examines Maja Lunde’s The History of Bees (2015) and Richard Powers’ The Overstory (2018). Through comparing these authors’ contrasting treatment of temporality, I argue that both novels perform crucial cultural work in destabilising myopic perspectives on human and environmental paradigms and depict human and more-than-human experiences of time. My article investigates how extensive scales and multiple temporalities can be imagined in literature. By illustrating the complexity of scale and time, Lunde and Powers combat narrow, anthropocentric depictions of nature in favour of holistic, multi-faceted depictions of nature. Lunde’s and Powers’ treatment of time illuminates methods that diversify perspectives of human citizenship in, and relationship to, a more-than-human world. Through examining each narrative’s multi-layering of temporalities, this article explores how The History of Bees and The Overstory each capture the complexities of ecological life in an attempt to enlarge and redirect attention to both the minute and cosmological layers of time.